ЖИЗНЬ СТЕПНЫХ ОЗЕР КАЗАХСТАНА. ЕСТЕСТВЕННАЯ ГИБРИДИЗАЦИЯ РЫБ - ФОРМА ВНУТРИПОПУЛЯЦИОННОЙ АДАПТАЦИИ (ҚазҰУ хабаршысы. Экология сериясы, 2016)
Introduction of carps and cazans into lakes with predominance of the crucian carps presence, is foster to increasing offish capacity of water body. Crossing between crucian carps and invading species (immigrants) do not occur.